Evaluation of in-situ Soil and Water Conservation Treatments on the Performance of Acid lime (Citrus aurantifolia Swingle) on Vertisols - Panigrahi, P; Srivastava, a K; Huchche, A D (Journal of Agricultural Engineering, 2005)
Different in-situ soil and water conservation treatments consisting of continuous trenching, continuous bunding, staggered trenching between the rows and control (without any soil and water conservation treatment) were evaluated during 2003-04 in 11 years old acid lime orchard at Nagpur. All the conservation treatments were effective in checking loss of runoff, soil and nutrients, which resulted in a favourable response of the plants in terms of better growth, fruit yield and quality, compared to those under the control. The treatment, continuous trenching produced the best response conserving 38% runoff, 32.28% soil loss, 32.44%N, 27.67% P, and 28.95% K over control, besides 18% higher fruit yield.